Role of T cells in the pathogenesis of atopic dermatitis. - Ogg, G (2009)
Our understanding of the pathogenesis of atopic dermatitis has been dramatically enhanced following the identification of the association with loss of function mutations in filaggrin, an epidermal protein thought to be important for cutaneous barrier integrity. However, it has also emerged that Th2 cytokines can influence barrier function, including through modulation of the expression of filaggrin, other structural proteins and peptides important for microbial barrier function. A picture is developing of a complex interplay between epidermal and non-epidermal susceptibilities that contribute to disease. Understanding the key components involved will be important for the identification of new approaches to treatment.